Design and development of a web-based interface for the Agricultural Policy Environmental eXtender (APEX) model. (January 2019) - Feng, Qingyu; Engel, Bernard A.; Flanagan, Dennis C.; Huang, Chi-hua; Yen, Haw; Yang, Lei
Abstract: The diffuse nature of nonpoint source (NPS) pollution as well as that of the effectiveness of best management practices (BMP) to control NPS pollution necessitates BMP evaluation at the field scale. In this study, a web interface was developed for application of the Agricultural Policy Environmental eXtender (APEX) model at the field scale. The interface contains background databases for field location, soil, agricultural management and climate across the contiguous United States. Users can specify properties to run the model for an individual field and compare the results under various land management and conservation practice choices. A case study was conducted to demonstrate the capability of the web interface for simulating various land management scenarios. This tool can help provide on-site information for NPS pollution management related policies and serve as a communication tool among scientists, engineers, and stakeholders. Highlights: An efficient web-interface for the APEX model was developed. Databases for model inputs and management operations can be systematically prepared. Multiple modeling outputs can be visibly demonstrated through the interface. Evaluation of hydrologic and water quality processes can be conducted efficiently.